Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Find the solution to the system of equations.
You can use the interactive graph below to find the solution.
\begin{cases} y=-4x-3 \\\\ y=-2x+1 \end{cases}









y=−4x−3
y=−2x+1


x=x=x, equals
y=y=y, equals


Sagot :

Answer:

x = -2, y = 5.

Step-by-step explanation:

y=−4x−3

y=−2x+1

Because y is common to both left sides:

-4x - 3 = -2x + 1

-4x + 2x = 1 + 3

-2x = 4

x = 4/-2

x = -2.

So y = -4(-2) - 3

= 8 - 3

= 5 .